A population health approach to workplace mental health: rationale, implementation and engagement - Kaylee T. Woodard; Allison M. Bailey; Aaron I. Esagoff; Maren S. Fragala; Joanna I. Hayward; Jennifer L. Hunter; Yea-Jen Hsu; Paul M. Kim; Matthew E. Peters; Susan M. Carr (Frontiers Media S.A., 2024)
ObjectivesTo describe a population health-based program to support employee and dependent mental health and learn from engagement trends.MethodsRetrospective analysis of a program utilizing an assessment of mental health risk. For scoring "at risk," a Care Concierge is offered to connect users with resources.ResultsParticipation was offered to 56,442 employees and dependents. Eight thousand seven hundred thirty-one completed the assessment (15%). Of those, 4,644 (53%) scored moderate or higher. A total of 418 (9%) engaged the Care Concierge. Factors that negatively influenced the decision to engage care included bodily pain, financial concerns. Positive influences were younger age, high stress, anxiety, PTSD and low social support.ConclusionProactive assessment plus access to a Care Concierge facilitates mental healthcare utilization. Several factors influence likelihood to engage in care. A better understanding of these factors may allow for more targeted outreach and improved engagement.